Distribution of Wildlife and Illegal Human Activities in the Lampi Marine National Park (Myanmar). (14th January 2019) - Bisi, Francesco; Gagliardi, Alessandra; Cremonesi, Giacomo; Colombo, Roberto; Mazzamuto, Maria Vittoria; Wauters, Lucas Armand; Preatoni, Damiano Giovanni; Martinoli, Adriano
Summary: Asian tropical forests are among the most affected by overhunting of wildlife species. Bushmeat is not just a source of food, but is also often seen as an income source due to the increasing regional demand for wildlife products. In this study, we assess for the first time the medium- and large-size vertebrate species present in Lampi Marine National Park (Myanmar) using camera traps and opportunistic sightings, and we use data from law enforcement patrolling to identify areas where poaching activities occur. Nineteen different terrestrial vertebrate species were observed in the Park, five of which are listed as globally threatened, while illegal activities were recorded at 107 locations. We estimated wildlife and human distributions using the maximum-entropy (i.e., MaxEnt) algorithm. Human activities were widely distributed in the Park, and areas selected by people were those at lower elevations and mainly in evergreen or semi-evergreen forests where most of the species occur. These models could improve knowledge of species presence and of the potential risk to wildlife associated with human activities. The modelling of wildlife and human presence proved to be useful for identifying areas that would receive special attention during patrolling, management and conservation actions.